(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
Small and Medium Enterprises (SMEs) are key enablers of a country’s economy. In recent investigations, innovation has shown major levels of competitiveness for this type of organizations and intellectual capital has been recognized as a significant factor for its performance improvement. Intellectual capital is classified into human, structural and relational. In particular, this research has the aim to explain if there is a relationship between intellectual capital and SMEs’ innovation. In this research methodology, the sample used was a total of 149 companies operating in Aguascalientes, México, with a size between 5 and 150 workers. The results indicate a positive relationship between the human, structural and relational capital and SMEs’ innovation. In this way, it has been identified the need to promote a strategy that enhance a systematic development of SMEs intellectual capital, mainly because of its impact and benefits provided for higher performance these organizations.